Confirmation and Identification of Listeria monocytogenes, Listeria spp. and Other Gram-Positive Organisms by the Bruker MALDI Biotyper Method: Collaborative Study, First Action 2017.10. (23rd November 2019) - Bastin, Benjamin; Bird, Patrick; Crowley, Erin; Benzinger, M Joseph; Agin, James; Goins, David; Sohier, Daniele; Timke, Markus; Awad, Marian; Kostrzewa, Markus
Abstract: The Bruker MALDI Biotyper® method utilizes matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS for the rapid and accurate confirmation and identification of Gram-positive bacteria from select media types. This alternative method was evaluated using nonselective and selective agar plates to identify and confirm Listeria monocytogenes, Listeria species, and select Gram-positive bacteria. Results obtained by the Bruker MALDI Biotyper were compared with the traditional biochemical methods as prescribed in the appropriate reference method standards. Sixteen collaborators from 16 different laboratories located within the European Union participated in the collaborative study. A total of 36 blind-coded isolates were evaluated by each collaborator. In each set of 36 organisms, there were 16 L. monocytogenes strains, 12 non- monocytogenes Listeria species strains, and 8 additional Gram-positive exclusivity strains. After testing was completed, the total percentage of correct identifications (to both genus and species level) and confirmation from each agar type for each strain was determined at a percentage of 99.9% to the genus level and 98.8% to the species level. The results indicated that the alternative method produced equivalent results when compared with the confirmatory procedures specified by each reference method.